Student monitoring system database for academic advisor / Mohamad Ezad Hafez Mohd Pahroraji ... [et al.] - Mohd Pahroraji, Mohamad Ezad Hafez; Abd Rashid, Ahmad Faiz; Abu Bakar, Muhammad Fauzan; Ayob, Mohd Asraf; Maarof, Khairul Anuar; Adnan, Amira Shazlin (2022)
In UiTM, each lecturer is assigned with a group of students and plays the role as an academic advisor. It is the duty of the academic advisors to monitor the academic activities, procedure, and performance of the group of students under their supervision. The academic advisors supervise every student in the group throughout the years of study until the students graduate. The academic advisors are responsible to be aware and update all information pertaining to the students academically and personally. However, the information is currently scattered all over online and offline sources. It could be hard and difficult for academic advisors to reach all the information for monitoring, especially when the information is required, and decisions need to be made immediately. Some information requires access through internet connection, and some requires manual access through various documents. To overcome this problem, the Student Monitoring System Database for Academic Advisor was developed and established using Microsoft Excel. In this system, databases such as year of admission, students’ information, marks interval, status for exam results, study plan, course validation, dashboard, students’ examination result, and link to relevant websites were provided. The database needs to be manually entered once though. Once entered, the database becomes one stop centre that could be accessed and referred to whenever required immediately. Mail merge feature from Microsoft Word could be integrated with the system to generate certificates. The database system could also link to Microsoft Power BI to display the performance dashboard in mobile phone to facilitate easy and mobile access for academic advisors.